2009
DOI: 10.1038/nphoton.2009.28
|View full text |Cite
|
Sign up to set email alerts
|

Green light emission in silicon through slow-light enhanced third-harmonic generation in photonic-crystal waveguides

Abstract: Slow light has attracted significant interest recently as a potential solution for optical delay lines and time-domain optical signal processing 1,2. Perhaps even more significant is the possibility of dramatically enhancing nonlinear optical effects 3,4 due to the spatial compression of optical energy 5,6,7. Two-dimensional (2D) silicon photonic crystal (PhC) waveguides have proven to be a powerful platform for realizing slow light, being compatible with on-chip integration and offering wide-bandwidth and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
390
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 558 publications
(400 citation statements)
references
References 34 publications
7
390
1
2
Order By: Relevance
“…The waveguide is terminated by tapers 32 to suppress residual reflections and improve coupling. Similar passive structures have been used for investigating slow-light propagation 3,4 and nonlinearities 7,8 , but in our case an active material is incorporated inside the membrane and the structures are designed such that the slowlight regime spectrally overlaps with the region where positive net material gain can be achieved by optical pumping. A schematic of the setup as well as scanning electron microscopy pictures of fabricated samples are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The waveguide is terminated by tapers 32 to suppress residual reflections and improve coupling. Similar passive structures have been used for investigating slow-light propagation 3,4 and nonlinearities 7,8 , but in our case an active material is incorporated inside the membrane and the structures are designed such that the slowlight regime spectrally overlaps with the region where positive net material gain can be achieved by optical pumping. A schematic of the setup as well as scanning electron microscopy pictures of fabricated samples are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…With enhanced light trapping, there are increased time delays and enhanced light-matter interactions, which are useful in nonlinear optics and laser excitation. 10,11,27,28 In Fig. 5(c), one can see that there are central transmission peaks induced by an additional phase shift along L 4 , which correspond to a group delay 2.1 times higher than that of the CSLR resonator without the additional phase shift in Fig.…”
Section: -7mentioning
confidence: 97%
“…[7][8][9] Moreover, the resulting group delay response and mode interaction are useful for enhancing light-material interaction and dispersion engineering in nonlinear optics. [10][11][12][13][14] Photonic resonators can be classified into two categories-travelling-wave (TW) resonators, exemplified by ring resonators, and standing-wave (SW) resonators represented by photonic crystal cavities, distributed feedback cavities, and Fabry-Pérot (FP) cavities. 3 The majority of work on mode splitting in photonic resonators has been based on TW resonators [15][16][17][18][19] although some recent work has investigated device structures consisting of both TW and SW resonators.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that certain plasmonic nanostructures can produce an enhanced nonlinear response when excited at their resonant frequency (1,2). Phase-matching requirements (3)(4)(5) for nonlinear optics in macroscopic media are usually optimally fulfilled at nanoscale dimensions [sinc 2 (Δk z/2) ∼1 for small z, where z is the propagation distance through the medium]. For plasmonic nanostructures, the most important property for the enhancement of nonlinear properties is their increased local fields at resonance, which can provide larger effective susceptibilities than their intrinsic material susceptibility.…”
mentioning
confidence: 99%